Full Wave Rectifier Circuit With IC Modification To Reduce DC Wave Ripple Output - Aulia, Mohammad Fadhi; Mulyadi, Adi (Universitas Panca Marga, 2023)
This paper presents a novel full-wave rectifier to reduce an output ripple of DC wave. Several filter variations have been applied, but the filter output produces a ripple wave output. Therefore, variations of IC 7812, 7815, 7818 and 7824 are proposed to reduce the ripple wave output. The full wave rectifier circuit is designed to regulate the diode output voltage, output current, VRMS and DC motor rotation. The results of applying the IC show that the output ripple can be reduced based on the voltage variation settings on each IC. The greater the variation in IC output voltage, the greater the output voltage, current, VRMS and motor rotation. Meanwhile, the ripple output shows variations in values of 0.252, 0.023, 0.025 and 0.023. The input voltage does not affect the full wave rectifier circuit even though the diode output voltage, current, rpm, VRMS and output ripple vary.